Secret Cardinal - Tom Grace (New York Vanguard Press, 2007)
Called in by the Vatican to examine the workings of the Vatican Library, former Navy SEAL Nolan Kilkenny soon discovers that Pope Leo has another mission in mind--to rescue a "secret" cardinal, a Chinese bishop imprisoned by the Chinese for some thirty years--and with the help of American Special Forces, the CIA, and the U.S. president, launches a daring rescue operation that could change history. 50,000 first printing.
Keywords: American fiction